Service utilization and HIV outcomes among transgender women receiving Ryan White Part A services in New York City. - Jacinthe A Thomas (Public Library of Science (PLoS), 2021)
Background Prior research has found evidence of gender disparities in U.S. HIV healthcare access and outcomes. In order to assess potential disparities in our client population, we compared demographics, service needs, service utilization, and HIV care continuum outcomes between transgender women, cisgender women, and cisgender men receiving New York City (NYC) Ryan White Part A (RWPA) services. Methods The analysis included HIV-positive clients with an intake assessment between January 2016 and December 2017 in an NYC RWPA services program. We examined four service need areas: food and nutrition, harm reduction, mental health, and housing. Among clients with the documented need, we ascertained whether they received RWPA services targeting that need. To compare HIV outcomes between groups, we applied five metrics: engagement in care, consistent engagement in care, antiretroviral therapy (ART) use, point-in-time viral suppression, and durable viral suppression. Results All four service needs were more prevalent among transgender women (N = 455) than among cisgender clients. Except in the area of food and nutrition services, timely (12-month) receipt of RWPA services to meet a specific assessed need was not significantly more or less common in any one of the three client groups examined. Compared to cisgender women and cisgender men, a lower proportion of transgender women were durably virally suppressed (39% versus 52% or 50%, respectively, p-value < 0.001). Conclusions Compared with cisgender women and cisgender men, transgender women more often presented with basic (food/housing) and behavioral-health service needs. In all three groups (with no consistent between-group differences), assessed needs were not typically met with the directly corresponding RWPA service category. Targeting those needs with RWPA outreach and services may support the National HIV/AIDS Strategy 2020 goal of reducing health disparities, and specifically the objective of increasing (to ≥90%) the percentage of transgender women in HIV medical care who are virally suppressed.